2010
DOI: 10.1111/j.1524-4725.2010.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolic Acid Peels Versus Amino Fruit Acid Peels in the Treatment of Melasma

Abstract: Based on the results of this study, GA and AFA peels for melasma therapy were efficacious, but the AFA peel was found to be less irritating and was better tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…It decreased significantly in both groups; adverse effects were less with amino fruit acid peels. [48]…”
Section: Newer Chemical Peelsmentioning
confidence: 99%
“…It decreased significantly in both groups; adverse effects were less with amino fruit acid peels. [48]…”
Section: Newer Chemical Peelsmentioning
confidence: 99%
“…[46] In a recent study on light-skinned patients, the amino fruit acid peels were found to be as effective as the GA peels and better tolerated. [47] However, there are no studies on dark-skinned patients to substantiate this finding.…”
Section: Chemical Peels For Melasma In Dark Skinmentioning
confidence: 99%
“…51 Both sides showed a statistically significant decrease in MASI 3 and 6 months from baseline (p < 0.05). They are carboxylated amino acids that have been found to be potent antioxidants and promising in treating photopigmentation.…”
Section: Chemical Peelsmentioning
confidence: 86%